Magnesium as an intrinsic component of human otoconia. (2nd September 2018) - Walther, Leif Erik; Wulfes, Jana; Blödow, Alexander; Kniep, Rüdiger
Abstract: Objectives: To investigate morphology changes of artificial otoconia (CGC) in the presence of magnesium during growth under in vitro conditions. Methods: Investigating human otoconia by environmental scanning electron microscope and determining their magnesium content by energy-dispersive X-ray microanalysis (EDX). Comparing structural and morphological data of human and artificial otoconia (CGC, Ca1 Mg0 ) without and with magnesium substitution (Ca1-x Mgx ). Results: EDX- and X-ray data reveals that the inorganic component in human otoconia consists of calcite containing a minor amount of magnesium substitution (Ca1-x Mgx ). CGC containing magnesium (length 397.0 ± 146.4 µm, diameter 325.6 ± 100.1 µm) are slimmer and significantly smaller ( p  < .01) than pure CGC (length 548.6 ± 160 µm, diameter 373.0 ± 110.4 µm) and reveal a significant influence on the final morphology. The length/diameter ratio is significantly higher by incorporation of magnesium into CGC (1.84 ± 0.25 µm versus 1.48 ± 0.11 µm in pure CGC, p  < .01), which brings the overall shape to a close relationship with human otoconia (1.98 ± 0.08 µm). Conclusions: Magnesium is an intrinsic component of human otoconia by partial substitution of calcium in the calcite crystal structure (Ca1-x Mgx ) and affects the development of the shape of artificial otoconia (calcite gelatin composites, CGC).